Smart Buildings Aggregator Bidding Strategy as a Negawatt Demand Response Resources in the Spinning Reserve Electricity Market - Safari A.; Tahmasebi M.; Pasupuleti J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Buildings; Commerce; Electric industry; Electric power transmission networks; Intelligent buildings; Scheduling; Smart power grids; Algebraic modeling; Consumption patterns; Demand response; Demand response resources; Negawatt; Network reliability; Spinning reserves; Triangulum; Power markets